Combining passive sampling with toxicity testing to evaluate potential ecotoxicological effects of pharmaceuticals in wastewater-impacted rivers - Ying Li; Wen Yang; Xi-qiang Zheng; Chi Yao; Yi Wu (Water Science and Engineering, 2021)
A passive sampling method was employed for time-integrative monitoring of five pharmaceuticals and one transformation product (TP) in rivers impacted by sewage treatment plants, in parallel with traditional sampling methods. Target pharmaceuticals, other than naproxen, were detected through passive sampling, with average concentrations in the range of 0.2–5.8 ng/L, and through active sampling, with average concentrations in the range of 0.5–21.7 ng/L. Meanwhile, the ecotoxicological effects of pharmaceuticals and TPs were assessed, including the formation of zebrafish embryos and expression of target genes, upon exposure of zebrafish embryos to sulfadiazine (SDZ) and its TP sulfacetamide, as well as two artificial mixed rivers. The exposure results showed negligible impacts of environmental levels of SDZ, while mimic mixture exposure disturbed the development of embryos and led to the alteration of the socs3, TNF-α, and IL-1β genes. The findings of this study indicated that although pharmaceutical concentrations in rivers receiving treated wastewater are low, the potential ecological effects on the aquatic environment require more attentions.